(untitled) (Revista Inclusiones, 2020)
This paper studies the issues of the index of economic trust construction in Russia. The work analyzed the characteristics of various trust indices used in foreign systems to assess the investment climate. The aim of the paper is to develop the methodology to determine the trust index in Russia to solve the problem of asymmetric information in shaping the socio-economic policy of for the subjects of management.